OBSERVATION OF SUPERNOVA REMNANT IC 443 WITH THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
We report observation of the supernova remnant (SNR) IC 443 (G189.1+3.0) with the Fermi Gamma-ray Space Telescope Large Area Telescope (LAT) in the energy band between 200 MeV and 50 GeV. IC 443 is a shell-type SNR with mixed morphology located off the outer Galactic plane where high-energy emission has been detected in the X-ray, GeV and TeV gamma-ray bands. Past observations suggest IC 443 has been interacting with surrounding interstellar matter. Proximity between dense shocked molecular clouds and GeV-TeV gamma-ray emission regions detected by EGRET, MAGIC, and VERITAS suggests an interpretation that cosmic-ray (CR) particles are accelerated by the SNR. With the high gamma-ray statistics and broad energy coverage provided by the LAT, we accurately characterize the gamma-ray emission produced by the CRs accelerated at IC 443. The emission region is extended in the energy band with theta(68) = 0 degrees.27 +/- 0 degrees.01(stat) +/- 0 degrees.03(sys) for an assumed two-dimensional Gaussian profile and overlaps almost completely with the extended source region of VERITAS. Its centroid is displaced significantly from the known pulsar wind nebula (PWN) which suggests the PWN is not the major contributor in the present energy band. The observed spectrum changes its power-law slope continuously and continues smoothly to the MAGIC and VERITAS data points. The combined gamma-ray spectrum (200 MeV < E < 2 TeV) is reproduced well by decays of neutral pions produced by a broken power-law proton spectrum with a break around 70 GeV.
CRIS-Team WoS Importer:2020-01-15